The Relationship Between Health Service Quality and Patient Satisfaction Level at the Old Tonsea Community Health Center in 2025. - Cyndi Delimah Y.M. Pasaribu; Christian Bertom Pajung; Prycilia Pingkan Mamuaja (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Patient satisfaction is the main indicator in measuring the success of health service delivery. Based on initial observations at the Tonsea Lama Health Center, even though it has been fully accredited, there are still complaints related to waiting time and comfort. This study aims to determine the relationship between the quality of health services and the level of patient satisfaction at the Tonsea Lama Health Center in 2025. Objective: To find out the relationship between the quality of health services and the level of patient satisfaction at the Tonsea Lama Health Center. Methods: This study used a quantitative method with a cross sectional design. The study population was outpatients at the Tonsea Lama Health Center with a sample of 73 respondents taken using consecutive sampling techniques. The research instrument uses a questionnaire that has been tested for validity and reliability. Data analysis was carried out univariately, bivariate using the Chi-Square test, and the Pearson correlation test. Results: The results of the univariate analysis showed that the majority of respondents were female (69.9%), aged 55-65 years (32.9%), high school education (72.6%), and worked as IRTs (52.1%). As many as 63.0% of respondents rated the quality of service in the good category and 63.0% of respondents were satisfied. The results of the Chi Square test showed a p-value = 0.000 (< 0.05), which means that there is a significant relationship between the quality of health care and the level of patient satisfaction. The Pearson correlation test showed a value of r = 0.824, which indicated a very strong and positive relationship. Conclusion: There is a significant and very strong relationship between the quality of health services and the level of patient satisfaction at the Tonsea Lama Health Center. The better the perception of the quality of the service provided, the higher the level of patient satisfaction.